Conservation Strategies in the Genus Hypericum via Cryogenic Treatment - Bruňáková, Katarína; Čellárová, Eva (Frontiers in Plant Science, 2016)
In the genus Hypericum, cryoconservation offers a strategy for maintenance of remarkable biodiversity, emerging from large inter- and intra-specific variability in morphological and phytochemical characteristics. Long-term cryostorage thus represents a proper tool for preservation of genetic resources of endangered and threatened Hypericum species or new somaclonal variants with unique properties. Many representatives of the genus are known as producers of pharmacologically important polyketides, namely naphthodianthrones and phloroglucinols. As a part of numerous in vitro collections, the nearly cosmopolitan Hypericum perforatum – Saint John’s wort – has become a suitable model system for application of biotechnological approaches providing an attractive alternative to the traditional methods for secondary metabolite production. The necessary requirements for efficient cryopreservation include a high survival rate along with an unchanged biochemical profile of plants regenerated from cryopreserved cells. Understanding of the processes which are critical for recovery of H. perforatum cells after the cryogenic treatment enables establishment of cryopreservation protocols applicable to a broad number of Hypericum species. Among them, several endemic taxa attract a particular attention due to their unique characteristics or yet unrevealed spectrum of bioactive compounds. In this review, recent advances in the conventional two-step and vitrification-based cryopreservation techniques are presented in relation to the recovery rate and biosynthetic capacity of Hypericum spp. The pre-cryogenic treatments which were identified to be crucial for successful post-cryogenic recovery are discussed. Being a part of genetic predisposition, the freezing tolerance as a necessary precondition for successful post-cryogenic recovery is pointed out. Additionally, a beneficial influence of cold stress on modulating naphthodianthrone biosynthesis is outlined.